STRATEGI EFEKTIF PELATIHAN PUBLIKASI KARYA ILMIAH GURU DI LINGKUNGAN SEKOLAH DASAR - Praditha, Riza; Ayu Gustiningsih, Diah; Aisyah, Nur; Agustuty, Lasty; Nurlinda, Nurlinda; Gani, Nurjaya; Asmawiyah, Asmawiyah (Arunika: Jurnal Pengabdian Masyarakat, 2024)
Scientific publication training is a strategic effort to improve teachers' professional competence, particularly in the areas of research and scientific writing. This activity was conducted at the UPTD SDN 22 Maros with the aim of helping teachers understand scientific writing techniques, journal publication procedures, and increasing their motivation to produce quality work. The training methods included lectures, discussions, hands-on practice, and mentoring. The results showed an increase in teachers' understanding of scientific paper structure, their ability to write articles, and their confidence in submitting articles to accredited journals. This activity is expected to contribute to the development of a culture of research and writing among elementary school teachers.